2022
DOI: 10.1017/s0890060422000154
|View full text |Cite
|
Sign up to set email alerts
|

Gamification of design thinking: a way to enhance effectiveness of learning

Abstract: The goal of this paper is to develop and test a gamified design thinking framework, including its pedagogical elements, for supporting various learning objectives for school students. By synthesizing the elements and principles of design, learning and games, the authors propose a framework for a learning tool for school students to fulfil a number of learning objectives; the framework includes a design thinking process called “IISC Design Thinking” and its gamified version called “IISC DBox”. The effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…When designing games for educational purposes, it is essential to know about the approaches available. Bhatt and Chakrabarti (2022) differ between gamification, serious games, and SG. In this publication, the focus is on SG aiming to represent processes or phenomena observed in reality within an education game.…”
Section: Characteristics and Development Of Simulation Gamesmentioning
confidence: 99%
See 3 more Smart Citations
“…When designing games for educational purposes, it is essential to know about the approaches available. Bhatt and Chakrabarti (2022) differ between gamification, serious games, and SG. In this publication, the focus is on SG aiming to represent processes or phenomena observed in reality within an education game.…”
Section: Characteristics and Development Of Simulation Gamesmentioning
confidence: 99%
“…A variety of games can be found in literature, including computer SG using animations, graphics, and an interactive environment e.g. for gear design and analysis based on adapted video games (Chang et al, 2016), simulations to represent challenges when setting up companies in competing markets (Braghirolli et al, 2016), simulations to teach the impact of design and production decisions on ecology, economy, and society, a Resin Puzzle game to undertake a variety of engineering design activities and design tasks using CAD/CAM technologies (Mavromihales et al, 2019), and games focussing on specific methods and development approaches like SCRUM (Fernandes and Sousa, 2010) or Design Thinking (Bhatt and Chakrabarti, 2022). While these games incorporate different game elements and didactics, c.f.…”
Section: Concepts and Benefits Of Gamification In Engineering Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Bhatt & Chakrabarti (2022) revealed that the integration of gamification in the learning process positively impacted students' engagement and motivation and contributed positively to their creativity and critical thinking skills.…”
Section: Theoretical Frameworkmentioning
confidence: 99%